Effect of clay particles on the behaviour of biofilms formed by Pseudomonas fluorescens - Vieira, M. J. (1995)
This paper presents results obtained with biofilms formed under turbulent flow by a mixed suspension ofPseudomonas fluorescens and kaolin particles and compares them with biofilms formed in the absence of clay particles. The results show that the presence of kaolin particles leads to: higher accumulation of biomass in biofilm systems; higher stability of the biofilms when substrate is suppressed; higher values of the respiratory coefficient of the suspended cell cultures; increase in the mass transfer rates throughout the biofilm thickness. The results suggest that the kaolin particles enhance microbial activity in the biofilm and may cause changes in the physical structure of the biofilm, making it a more strong and open matrix.